Characterization of Activated Carbon from Industrial Solid Waste Agar with a Different Activator Concentrations - Khuril Zaqyyah; Sri Subekti; Mirni Lamid (Journal Omni-Akuatika, 2020)
Production of seaweed processing generates a huge amount of waste, either waste solid or liquid waste. For solid waste contains a lot of organic carbon derived from cellulose or hemicellulose. Therefore, the solid waste that has the potential as a raw material of activated carbon. This study aims to determine the characteristics of the activated carbon produced from solid waste agar and determine the optimal concentration of activator that produced the best characteristics of the activated carbon. The treatment used is a different activator concentration which is designed using completely randomized design (CRD) with five treatments and four replications. The results showed the five treatments are significant differences in the characteristics of the ash and pure active carbon content. This study shows that the manufacture of activated carbon industrial solid waste agar with a different activator concentration influence on the characteristics of the active carbon with ash content parameter and pure active carbon content. The concentration of activator that can provide the highest value of pure activated carbon is in P5 with a concentration of 6 M. Based on this study are advised to do further research on how to lower the ash content of the activated carbon from solid waste agar.